The gendered effect of populism on innovation - Tang, Jintong; Ye, Wenping; Hu, Mingzhi; Zhang, Stephen X.; Khan, Shaji A. (Journal of Business Venturing, 2024)
This research addresses the impact of the remarkable rise in populism on innovative new ventures. Integrating institutional theory with gender role congruity theory, we reason that the surge of populist discourse by a nation's top political leaders decreases the innovativeness of new ventures, and this negative relationship is more pronounced for women entrepreneurs. We also consider two critical yet overlooked institutions, gender inequality and grammatical gender marking in the dominant languages that entrepreneurs speak, and propose that they reinforce this negative relationship. Data from 69,406 observations of entrepreneurs across 40 countries during the period of 2005–2018, analyzed with a difference-in-differences (DiD) design, support our hypotheses. Theoretical and policy implications are discussed for the challenges of promoting innovation among women entrepreneurs, in countries with greater gender inequality and where the dominant language exhibits greater intensity of grammatical gender marking, with populism on the rise worldwide.